Remarkable Activation of an Alkyne [2+2+2]-Cycloaddition Catalyst, 2-Iminomethylpyridine (dipimp)/CoCl2·6H2O/Zn, by a Phthalate Additive - Sugiyama, Yu-ki; Kariwa, Takuma; Sakurada, Tetsuya; Okamoto, Sentaro (Synlett, 2012)
A catalyst for alkyne [2+2+2]-cycloaddition reactions, 2-(2,6-diisopropylphenyl)iminomethylpyridine (dipimp)/CoCl2·6H2O/Zn, can be effectively activated by addition of a catalytic amount of dialkyl phthalate to enable reactions that cannot proceed under unactivated conditions. The activation by adding phthalate was ligand- and solvent-dependent, and it was unique to dipimp and N-methyl-2-pyrrolidone (NMP). With use of diphosphine ligand instead of dipimp or with use of tetrahydrofuran (THF) instead of NMP, no activation by a phthalate additive was observed. This simple method of catalyst activation with use of inexpensive, commercially available compounds is highly practical and may find many applications.
Keywords: cycloaddition; homogeneous catalysis; alkynes; esters; ligands; phthalate; catalyst activation